Fortification of elephant ginger extract (Zingiber officinale var Roscoe) in the production of mochi with variations of glutinous rice flour – white sweet potato flour (Ipomea batatas L): Fortifikasi ekstrak jahe gajah (Zingiber officinale var Roscoe) dalam pembuatan mochi dengan variasi tepung ketan-tepung ubi jalar putih (Ipomea batatas L) - Nanda Anggraini; Vivi Nuraini; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2025)
Mochi is a cake made from glutinous rice flour with other ingredients and then steamed. White sweet potato flour is used as a substitute because it contains high levels of fiber, with the addition of elephant ginger extract, which is expected to be able to neutralize the unpleasant taste and scent of white sweet potato flour. The aim of this study was to determine the right formulation in order to obtain white sweet potato flour substitution mochi and a high concentration of elephant ginger extract. This study used a completely randomized design (CRD), which consisted of two factors, namely the concentration of glutinous rice flour and white sweet potato flour (90:10, 80:20, and 70:30) and the percentage of elephant ginger extract (to 100 ml of water) (1.5%, 3%, and 4.5%). The best results of the chemical analysis were white sweet potato flour 30 g and ginger extract 4.5%, with a moisture content of 23.66%, an ash content of 0.25%, a total sugar content of 7.64%, and fiber of 2.60%. Based on the results of the physical analysis, the colour L*47.62 (bright brown), a* -4.68 (slightly green), b* 12.20 (yellowish) and a hardness value of 8.90 N, gumminess of 6.27 N, chewiness of 1.73 N, cohesiveness of 0.71 N, and adhesiveness of 1.17 N. Mochi with white sweet potato flour substitution and concentration of elephant ginger extract can be a nutritions food and a source of fiber.